2019
DOI: 10.3171/2018.12.spine18970
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone trajectory screws used to save failed traditional trajectory screws in the osteoporotic lumbar spine and vice versa: a human cadaveric biomechanical study

Abstract: OBJECTIVETraditional trajectory (TT) screws are widely used in lumbar fixation. However, they may require revision surgery in some instances, especially in patients with osteoporotic spines. Cortical bone trajectory (CBT) screws may potentially be used to rescue a failed TT screw and vice versa in nonosteoporotic spines. This study aimed to investigate whether a CBT screw can salvage a compromised TT screw in osteoporotic lumbar spines and vice versa. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Through CT examination, Teo et al found that the thickness, number and space of bone trabeculae in porcine spine and human spine were very similar [21] , as shown in Table .4. In addition, the study of Zhang et al used spinal specimens of human with osteoporosis, and the results of maximum insertional torque and pullout load were similar to those of this study [22] , as shown in Table .5. On the other hand, rapid decalcitration of porcine spine with EDTA solution is also a common method, which can be used to prepare a reproducible in vitro model of osteoporotic animal vertebral body in a simple and rapid manner [8] .…”
Section: Results and Analysissupporting
confidence: 82%
“…Through CT examination, Teo et al found that the thickness, number and space of bone trabeculae in porcine spine and human spine were very similar [21] , as shown in Table .4. In addition, the study of Zhang et al used spinal specimens of human with osteoporosis, and the results of maximum insertional torque and pullout load were similar to those of this study [22] , as shown in Table .5. On the other hand, rapid decalcitration of porcine spine with EDTA solution is also a common method, which can be used to prepare a reproducible in vitro model of osteoporotic animal vertebral body in a simple and rapid manner [8] .…”
Section: Results and Analysissupporting
confidence: 82%
“…The CBT is a relatively new spinal fixation technique involving a unique caudocephalad and medial-to-lateral screw trajectory (Santoni et al, 2009). The biomechanical properties of CBT screws are superior to those of traditional pedicle screws (Santoni et al, 2009;Sansur et al, 2016;Zhang et al, 2019). Therefore, CBT is a better choice in treating osteoporotic patients (Ueno et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vivo insertion torque of the CBT screws increased by 1.71 times compared to that of conventional PS. Zhang et al 12 found that CBT screws had better biomechanical performance in pullout strength and toggle tests than did conventional PS. It is known that CBT screw/rod structures provide almost the same stability as conventional PS-rod structures.…”
Section: Discussionmentioning
confidence: 99%